Pengaruh Gaya Kepemimpinan, Kompensasi dan Komitmen Organisasi Terhadap Kepuasan Kerja pada PT. Kresna Karya Basecamp Akah Klungkung - Tiksnayana Vipraprastha; Bagus Nyoman Kusuma Putra (Universitas Triatma Mulya, 2024)
The aim of this research is to find out whether leadership style, compensation and organizational commitment have an effect on job satisfaction at